2014
DOI: 10.1007/s00441-014-2036-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of choline and acetylcholine transporters in synovial tissue and cartilage of patients with rheumatoid arthritis and osteoarthritis

Abstract: Increasing evidence is showing that the non-neuronal cholinergic system plays an important role in the pathology of rheumatoid arthritis (RA). Choline transport into the cell is the rate-limiting step for the synthesis of acetylcholine (ACh), which can be released directly or in vesicles from the cell. However, in the human joint little is known about choline import or the release of ACh from the cell. Thus, we analyze the expression of members of the organic cation transporter (OCT), of the newly discovered c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 64 publications
0
31
0
1
Order By: Relevance
“…In particular, Song et al [29] have demonstrated that knockdown of CTL4 in lung cancer cells decreases ACh synthesis while increasing expression of CTL4 increases choline transport and ACh synthesis. Besides CTL4, the organic cation transporter (OCT) 1 and 3 have also been linked to non-neuronal ACh synthesis, as demonstrated by expression in cell types that synthesize ACh but do not express CHT1 [30,31]. …”
Section: Targeting Choline Transport Needed For Ach Synthesis In Lmentioning
confidence: 99%
“…In particular, Song et al [29] have demonstrated that knockdown of CTL4 in lung cancer cells decreases ACh synthesis while increasing expression of CTL4 increases choline transport and ACh synthesis. Besides CTL4, the organic cation transporter (OCT) 1 and 3 have also been linked to non-neuronal ACh synthesis, as demonstrated by expression in cell types that synthesize ACh but do not express CHT1 [30,31]. …”
Section: Targeting Choline Transport Needed For Ach Synthesis In Lmentioning
confidence: 99%
“…Peptide sequences from SLC18A3 were present in all six patients. Previous studies have shown that various choline and acetylcholine transporters are expressed in synovial tissue and cartilage from patients with rheumatoid arthritis and OA, however, SLC18A3 was absent …”
Section: Discussionmentioning
confidence: 88%
“…Previous studies have shown that various choline and acetylcholine transporters are expressed in synovial tissue and cartilage from patients with rheumatoid arthritis and OA, however, SLC18A3 was absent. 40 SH3 and multiple ankyrin repeat domains protein 2 (SHANK2) is involved in synaptic plasticity through its regulation of NMDA receptors as well as regulating the spine. 41 SHANK2 endogenous peptide sequences were present in all six patients.…”
Section: Neuropeptide Signalling Pathways In Oamentioning
confidence: 99%
“…Synoviocytes and macrophages express a range of nicotinic subunits including alpha-7 homopentamer [16,73,74]. The OA synovial membrane also expresses choline transporters and muscarinic receptors 1, 3, 4, and 5 and nicotinic subunits alpha-3, -5, -6, -7, -9, and -10 [17,75]. Therefore, the synovium may be able to produce and respond to Ach stimulation.…”
Section: Pns and Synoviummentioning
confidence: 99%